Circulating lipids and glycaemic control in insulin dependent diabetic children. Issue 2 (August 1994) - Azad, K; Parkin, J M; Court, S; Laker, M F; Alberti, K G
Abstract : The prevalence of dyslipidaemia in children with insulin dependent diabetes mellitus (IDDM) and its relation to glycaemic control was studied in a group of 51 diabetic children and a control population of 132 schoolchildren. The prevalence of dyslipidaemia in the fasting state was increased in the diabetic group (39%) compared with control subjects (17%). Serum cholesterol concentration alone was raised in 25% of diabetic subjects while serum cholesterol and triglycerides were raised in 14%, compared with 16% and 0.7% respectively in control subjects. Serum total cholesterol (5.1 v 4.5 mmol/l), low density lipoprotein cholesterol (3.2 v 2.6 mmol/l), non-esterified fatty acids (0.91 v 0.50 mmol/l), and triglycerides (0.94 v 0.76 mmol/l) were higher in diabetic children. Serum total cholesterol, triglycerides, and apolipoprotein (apo)B concentrations increased with worsening control, while serum high density lipoprotein cholesterol and apoA-I concentrations were unaltered. There were also positive correlations between glycated haemoglobin and total cholesterol, triglycerides, and apoB in diabetic children. Thus, abnormalities in circulating lipids are common in young subjects with IDDM but largely disappear if blood glucose concentrations are reasonably controlled.